Extraintestinal Clostridioides difficile Infections: Epidemiology in a University Hospital in Hungary and Review of the Literature - Edit Urbán; Gabriella Terhes; Márió Gajdács (MDPI AG, 2020)
Extraintestinal manifestations of Clostridioides difficile infections (CDIs) are very uncommon, and according to the literature, poor outcomes and a high mortality have been observed among affected individuals. The objective of this study was to investigate the incidence rate of extraintestinal infections caused by C. difficile (ECD) in a tertiary-care university hospital in Hungary. During a 10-year study period, the microbiology laboratory isolated 4129 individual strains of C. difficile; among these, the majority were either from diarrheal fecal samples or from colonic material and only n = 24 (0.58%) were from extraintestinal sources. The 24 extraintestinal C. difficile isolates were recovered from 22 patients (female-to-male ratio: 1, average age: 55.4 years). The isolates in n = 8 patients were obtained from abdominal infections, e.g., appendicitis, rectal abscess or Crohn’s disease. These extraintestinal cases occurred without concomitant diarrhea. In all, but two cases C. difficile was obtained as a part of a polymicrobial flora. Our isolates were frequently toxigenic and mostly belonged to PCR ribotype 027. Resistance to metronidazole, vancomycin, clindamycin and rifampin were 0%, 0%, 20.5% and 9.7%, respectively. The increasing amount of reports of C. difficile extraintestinal infections should be noted, as these infections are characterized by a poor outcome and high mortality rate.